Rumah Meditasi di Desa Pecatu, Badung - Sutriadi, Sella Angelita; Agusintadewi, Ni Ketut; Susanta, I Nyoman (Jurnal Arsitektur Universitas Udayana, 2022)
Meditation is one solution to overcome stress, anxiety and depression, by getting rid of disturbing thoughts and making the body more relaxed. Meditating while traveling is another alternative that can be done to relieve stress. The Pecatu area is a tropical area with stunning beaches and suitable as a place to meditate. The Indoor Meditation Hall is one of the buildings in the Meditation House in which the main activity is meditation, so it requires special attention in its design. The purpose of this study is to analyze how the Indoor Meditation Hall applies a bioclimatic architectural approach to site landscaping, appearance and interior. The method in this research is descriptive analysis method which is equipped with a design visualization scheme. The result of this research is the design of the Indoor Meditation Hall which applies a bio-climatic architectural approach in several aspects so that this facility is able to accommodate a number of activities related to tranquility and can provide thermal comfort for the community in it.